+0  
 
0
149
1
avatar+589 

Given f(x)=2x2−5x−3 and g(x)=2x2+x .

What is (fg)(x) ?

 Feb 28, 2018
 #1
avatar+94526 
+2

f(x)=2x^2−5x−3 and g(x)=2x^2+x

 

(f * g) (x)  =

 

2x^2(2x^2 + x)  - 5x(2x^2 + x)  -3(2x^2 + x)

 

4x^2 + 2x^3  - 5x^3 - 5x^2 - 6x^2 - 3x

 

-3x^3  - 7x^2 - 3x

 

 

cool cool cool

 Feb 28, 2018

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.